EMPOWERING CUB SCOUTS THROUGH HOLISTIC NURSING TO PREVENT SEXUAL HARASSMENT WITH THE EDUCATIONAL GAME SNAKES AND LADDERS - Surya Putri, Novita; Anisa Firmanti, Tria; Pramesti Wilujeng, Atik; Rudiyanto; Syahbana, Ali; Supriyanto (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2025)
Background: The iceberg phenomenon in cases of sexual harassment occurred in Banyuwangi. Anti-sexual harassment education for children increases understanding that has a positive impact, such as good behavior that is carried into adulthood, free from sexual deviations, and can contribute to solving sexual problems in the future. This community service aims to differentiate the alert scout members of SDN 1 Mojopangung in understanding anti-sexual harassment with a holistic nursing approach. Method: The method used in this community service is game-based learning (GBL)—empowered participants in cub scouts, namely grade 4 and 5 students at SDN 1 Mojopangung. There are 15 class 4 students and 15 class 5 students. The total number of participants empowered in this community service is 30 students. Result: Based on the pre-test results, most students’ understanding of sexual harassment is poor (60%). Anti-bullying snakes and ladders training participants were given material on preventing sexual harassment through a holistic nursing approach involving physical, mental, emotional, and spiritual aspects. Most students had a good understanding (90%) after being given material and training in understanding anti-sexual harassment using the anti-sexual harassment snakes and ladders board. Conclusion: Approach with snake and ladder games that contain the words anti-sexual harassment and acts of sexual harassment. It is easy for 4th and 5th-grade elementary school students to adapt and understand.